Nostalgia and degeneration of splendour in Hedayat’s The Blind Owl - Pedram Lalbakhsh; Pouria Torkamaneh (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The Arab invasion of Sassanid’s territory in 637 A.D. was the cause for many conspicuous changes in the social and political aspects of Persians’ life. One of the most distinct changes was the gradual degeneration of Persians’ assumed cultural and religious legacy that considered Zoroastrianism as the true religion and the Aryan race as a pure and superior one. However, centuries of struggle and skirmishes in part of those interested in the revival of their assumed ancient past did not lead to the restoration of the type of social esteem and stability they favoured for their country. In his modernist novel, The Blind Owl, Sadeq Hedayat sounds like the spokesperson of this faction, voicing their lamentation upon the identity loss and the degeneration of the glorious past they nostalgically advocated and dreamed. Accordingly, building upon Dennis Walder’s theory of Postcolonial Nostalgias, the authors argue that Hedayat’s novella offers a couple of tales as platforms to nostalgically lament the aforementioned undesirable changes that these individuals had to encounter and endure. As such, the first tale presents the bitter reality of a world where nostalgia is prevailing and affecting the invaded nation, while the second tale pictures the degenerated splendour and the tarnished image of the past immediately after the arrival of the invaders.